Giant fibroma of the lesser omentum: report of a rare case - Iusco, D.; Donadei, E.; Sgobba, et al., G. (Acta Biomedica Atenei Parmensis, 2005)
We report a case of a 43 years old male that presented to emergency room for epigastric and mesogastric pain associated with a palpable abdominal mass. Explorative laparotomy showed a well capsulated tumour of the lesser omentum, sized 20 x 16 x 10cm. Histologically the mass was charaterized by thick fibrous capsula, with areas of moderate cellularity alternated to areas of sclerosis, spots of hemorragies and infartual necrosis, spindle-shaped cells within collagen bundles that did not present mitotic activity or atipies and showed a low proliferation index with Ki 67 and histochemical positivity for CD 34 and negativity for CKit, anti-smooth cell and S100 antigen. Final diagnosis: solitary fibroma of the lesser omentum. To our knowledge only one case of lesser omentum fibroma has been reported in litterature.